Hemostatic agents in periapical surgery: The systematic review - Z. S. Khabadze; D. A. Nazarova; E. S. Shilyaeva; A. P. Kotelnikova; Yu. A. Bakayev; S. M. Abdulkerimova; Kh. O. Omarova (LLC "Endo Press", 2021)
Several agents have been used to secure hemostasis during periapical surgery. Their efficacy, biological response and side effects differ from each other.Aim. Of this review article is to assess systematically the available scientific evidence about the clinical response after using hemostatic agents during apical surgery.Materials and methods. The study of publications was produced in the electronic databases such as Google Scholar, PubMed during a systematic review of the literature. Included articles contain information about using hemostatic agents during periapical surgery and their adverse effects. The publication date criterion was selected from January 2006 to September 2021.Results. 55 articles were viewed during the review. After analyzing the literature for inclusion criteria, the total number of publications has become 10.Conclusions. According to literature data, different hemostatic agents are used during periapical surgery, but there weren't any inflammatory reactions while using calcium sulfate.